ANALISIS TINGKAT PENDAPATAN DEBITUR KREDIT MODAL KERJA (KMK) PADA PT BANK RAKYAT INDONESIA UNIT PASAR SWADAYA TIMIKA - Asrawati Asrawati; Daniel Nemba Dambe (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2018)
The aim this research to determine the difference in income on the working capital creditors (KKM) before and after receiving credit. Data collected by using technique: (1) observation that writer collect data by looking directly. (2) Questionnaire is by using a list of written questions that contain indicators of each variable. (3) interviews by asking questions. (4) documentation that is collecting data about debtors’ income before and after receiving credit from PT Bank Rakyat Indonesia Timika self-help market unit. To know the difference of opinion on debtors working capital credit (KMK) before and after receiving credit is used hypothesis testing of sign (sign test). the test mark used is the wilcoxon match pairs test. The result of the analysis shows that the acceptance of working capital credit (KMK) from PT Bank Rakyat Indonesia self-help unit is very influential. This happens because increased income after receiving credit is very influential. This happens because the increase in income after receiving credit is very significant to develop a business or working capital on the debtor.from the result of this reserach with 25 respondents and tested using the sign test wilcoxon seen that positive sign (+) greater than 323,5 negative sign (-) only 1,5.